(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The research aims to develop learning media through traditional Rimau Langkat games. Nowadays, character education and cultural literacy are needed to create a generation that has cooperation, togetherness, and nationalism for each other and thus local wisdom has values that can be used to teach character education. This research is research and development (R&D) with the 4 D design proposed by Sivasailam Thiagarajan. 4 D design consists of define, design, development, and dissemination. The research involved experts in learning media, Langkat culture, and Rimau Langkat Games to assess the digital storytelling. The sample is fourth-semester students in English Department Study Program, STKIP Al Maksum. The research used one group pre-test post-test to know the influence of the electronic module in teaching character education to the students. Based on the discussion, the expert in learning media, Langkat culture, and language was assessed electronically in the two stages. In the first stage, the electronic module was invalid the score range was 58%. In the second stage, the electronic module was valid the score range was 90%. Furthermore, based on the t-test, the electronic module was effective to teach character education to the students.